Packing forces in dichloridobis(3, 5‐diphenyl‐1H‐pyrazole‐κN2)cobalt(II) dichloromethane hemisolvate. Issue 8 (21st July 2014) - Nyamato, George S.; Ojwach, Stephen O.; Akerman, Matthew P.
<x xml:space="preserve">Abstract</x> The title compound, [CoCl2(C15H12N2)2]·0.5CH2Cl2, was crystallized from a binary mixture of dichloromethane and hexane and a dimeric supramolecular structure was isolated. The CoII centre exhibits a distorted tetrahedral geometry, with two independent pyrazole‐based ligands occupying two coordination sites and two chloride ligands occupying the third and fourth coordination sites. The supramolecular structure is supported by complementary hydrogen bonding between the pyrazole NH group and the chloride ligand of an adjacent molecule. This hydrogen‐bonding motif yields a ten‐membered hydrogen‐bonded ring. Density functional theory (DFT) simulations at the PBE/6‐311G level of theory were used to probe the solid‐state structure. These simulations suggest that the chelate undergoes a degree of conformational distortion from the lowest‐energy geometry to allow for optimal hydrogen bonding in the solid state.